Optimasi Temperatur Cooling Water Pada 25ºC Dan Hot Water Pada 60 ºC Dengan Variasi Waktu Siklus Pada Sistem 2 Bed Adsorption Chiller - Saragih, Krist Mamre; Martin, Awaludin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Adsorption chiller has one of the solution related to enviromental issues by conventional refrigeration. This paper presented the optimization temperature cooling water and hot water from sistem adsorption chiller. Performance of adsorption chiller influenced by temperature hot water inlet and temperature cooling water inlet. To optimization temperature hot water inlet, temperature cooling water stay at 30ºC and to optimization temperature cooling water inlet, temperature hot water stay at 65ºC. According to this research temperature optimal hot water inlet 60ºC in time cycle 700s with COP 0.36% and cooling power 0.72kW but temperature optimal cooling water inlet 25ºC in time cycle 700s with COP 0.31% and cooling power 0.73kW.Keyword : Adsorption chiller, Cooling water, Hot water, COP, Cooling power